2009
DOI: 10.1590/s1519-69842009000100004
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and seasonality of fruit flies (Diptera: Tephritidae and Lonchaeidae) and their parasitoids (Hymenoptera: Braconidae and Figitidae) in orchards of guava, loquat and peach

Abstract: This work was carried out in orchards of guava progenies, and loquat and peach cultivars, in Monte Alegre do Sul, SP, Brazil, in 2002 and. Guavas and loquats were bagged and unbagged bi-weekly and weekly, respectively, for assessment of the infestation period. Peach was only bagged weekly. The assays started when the fruits were at the beginning of development, but still green. Ripe fruits were taken to the laboratory and placed individually into plastic cups. McPhail plastic traps containing torula yeast wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
39
1
11

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(61 citation statements)
references
References 20 publications
5
39
1
11
Order By: Relevance
“…A. fraterculus was by far the most frequent species in all collections in this region. Our findings corroborate previous studies that show this species was also the most frequently recovered from systematic collections of guavas during the period of one to five years (SOUZA-FILHO et al, 2007;SILVA et al 2010) as well as from traps (DUTRA et al, 2009). In the southern region, guava was also infested by three Anastrepha species, A. fraterculus, A. sororcula, and A. zenildae, while Surinam cherry was infested by A. fraterculus and A. sororcula.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…A. fraterculus was by far the most frequent species in all collections in this region. Our findings corroborate previous studies that show this species was also the most frequently recovered from systematic collections of guavas during the period of one to five years (SOUZA-FILHO et al, 2007;SILVA et al 2010) as well as from traps (DUTRA et al, 2009). In the southern region, guava was also infested by three Anastrepha species, A. fraterculus, A. sororcula, and A. zenildae, while Surinam cherry was infested by A. fraterculus and A. sororcula.…”
Section: Resultssupporting
confidence: 93%
“…It is noteworthy that guava is infested by the highest diversity of fruit flies in Brazil, C. capitata and 11 species of Anastrepha (RAGA et al, 2006;SOUZA FILHO et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…McAlpine & Steyskal (1982) also found N. certa in I. vera, and Souza-Filho et al (2009) recorded this species in orchards of P. guajava. N. certa has already been registered in fifty host fruits, belonging to seventeen plant families ( Table 2) Table 2).…”
Section: Discussionmentioning
confidence: 92%
“…In a previous study carried out in the municipality of Monte Alegre do Sul, Souza-Filho et al (2009) reported eight species during a sampling period of one year. Silva et al (2006) carried out a two-year study in two locations in the Southern Brazil, and reported five Neosilba species.…”
Section: Discussionmentioning
confidence: 99%